1998
DOI: 10.1590/s0100-879x1998001000006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metabolic acidosis on renal tubular sodium handling in rats as determined by lithium clearance

Abstract: Systemic metabolic acidosis is known to cause a decrease in salt and water reabsorption by the kidney. We have used renal lithium clearance to investigate the effect of chronic, NH 4 Cl-induced metabolic acidosis on the renal handling of Na + in male Wistar-Hannover rats (200-250 g). Chronic acidosis (pH 7.16 ± 0.13) caused a sustained increase in renal fractional Na + excretion (267.9 ± 36.4%), accompanied by an increase in fractional proximal (113.3 ± 3.6%) and postproximal (179.7 ± 20.2%) Na + and urinary K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
2
8
0
3
Order By: Relevance
“…Since we performed the present experiments using whole kidney structure, our studies were not specifically designed to determine the effects of metabolic acidosis on Na þ transport mechanisms along particular nephron tubule sites nor to correlate Na þ patterns with altered solute and water tubule handling. Nevertheless, previous experiments demonstrating altered renal sodium handling [25,26] may provide evidence for a reciprocal relationship between the level of efficiency of renal mitochondrial activity and ion tubule transport. Therefore, we hypothesize that the mild uncoupling and higher capacity for Ca 2þ accumulation represents an adaptation of the mitochondria to cope with conditions of oxidative stress and high cytosolic Ca 2þ , which are associated with NH 4 Cl toxicity in renal cells.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Since we performed the present experiments using whole kidney structure, our studies were not specifically designed to determine the effects of metabolic acidosis on Na þ transport mechanisms along particular nephron tubule sites nor to correlate Na þ patterns with altered solute and water tubule handling. Nevertheless, previous experiments demonstrating altered renal sodium handling [25,26] may provide evidence for a reciprocal relationship between the level of efficiency of renal mitochondrial activity and ion tubule transport. Therefore, we hypothesize that the mild uncoupling and higher capacity for Ca 2þ accumulation represents an adaptation of the mitochondria to cope with conditions of oxidative stress and high cytosolic Ca 2þ , which are associated with NH 4 Cl toxicity in renal cells.…”
Section: Discussionmentioning
confidence: 94%
“…In this regard, we have previously shown that chronic metabolic acidosis, caused by NH 4 Cl feeding, leads to nephron hypertrophy and to a decreased watersalt reabsorption by the kidneys [1,25,26]. Since renal ion tubule transport is highly dependent on mitochondrial energy and because mitochondria have been implicated in a variety of metabolic disorders, we examined mitochondrial energy-linked functions in chronic metabolic acidotic rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 or tubular function [25][26][27][28][29] which can result in an altered renal handling of sodium. [30][31][32][33][34][35][36]101 Surprisingly, while use of diuretics are well known to make the FeNa unreliable, [35][36][37][38] other drugs, such as amphotericin, that are known to cause proximal tubular damage may not. 39 Rarely liver disease can result in prerenal azotemia with an elevated FeNa because of sodium bicarbonate wasting from alkalosis 30 or alternatively because of loss of urea production that is necessary for water reabsorption and urine concentration.…”
Section: Ureamentioning
confidence: 99%
“…Similarly, chronic (but not acute) respiratory acidosis is associated with a decrease in FeNa because of sodium bicarbonate generation and conservation by the tubules. 32 Chronic metabolic acidosis may also result in sodium wasting, 33,34 presumably because of a different mechanism where acidosis may disrupt active transport. Surprisingly, while use of diuretics are well known to make the FeNa unreliable, [36][37][38][39] other drugs, such as amphotericin, that are known to cause proximal tubular damage may not.…”
Section: Fenamentioning
confidence: 99%